A Case of Hemiabdominal Myoclonus. (October 2015) - Nociti, Viviana; Servidei, Serenella; Luigetti, Marco; Iorio, Raffaele; Lo Monaco, Mauro; Mirabella, Massimiliano; Frisullo, Giovanni; Della Marca, Giacomo
Myoclonus consists of sudden, brief, involuntary jerky muscular contractions. Central and peripheral nervous system lesions are involved in the pathogenesis of this movement disorder. Symptomatic or secondary spinal myoclonus is the most common form. A 68-year-old woman was diagnosed with hemiabdominal spinal myoclonus. Occasional and very mild involuntary repetitive movements of the hemiabdomen began immediately after surgery for uterine cancer. After surgery for laparocele, secondary to the uterine cancer surgery, performed under spinal anesthesia, there was severe worsening of movements. Neuroradiological investigations failed to demonstrate spinal injury, while neurophysiological studies showed impairment of the right central somatosensory pathway. Considering the low resolution of magnetic resonance imaging in the evaluation of thoracic level, we suggest an extensive neurophysiological evaluation in patients with spinal myoclonus.